2009
DOI: 10.1111/j.1464-0597.2008.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Abusive Supervision in Advising Relationships: Investigating the Role of Social Support

Abstract: The present study examines the consequences of abusive supervision in an educational setting. The study contrasts the cross-domain stress-buffering hypothesis with the within-domain stress exacerbation hypothesis in examining the moderating role of advisor and team member support on the relationship between abusive supervision and student outcomes in student-advisor relationships. Using a temporal research design, results provided support for both hypotheses. In support of the stress exacerbation hypothesis, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
141
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(157 citation statements)
references
References 54 publications
13
141
1
2
Order By: Relevance
“…However, we argue that the strength of the effect of each action tendency on behavior depends on individual and situational factors. Thus, our model allows for both action tendencies to operate in tandem and for the possibility that envy's consequences may entail behavior traditionally viewed as malicious, behavior traditionally viewed as benign, and in many instances some combination of the two (Duffy, Ganster, & Pagon, 2002;Hobman, Restubog, Bordia, & Tang, 2009).…”
Section: Our View: Envy As Painmentioning
confidence: 99%
“…However, we argue that the strength of the effect of each action tendency on behavior depends on individual and situational factors. Thus, our model allows for both action tendencies to operate in tandem and for the possibility that envy's consequences may entail behavior traditionally viewed as malicious, behavior traditionally viewed as benign, and in many instances some combination of the two (Duffy, Ganster, & Pagon, 2002;Hobman, Restubog, Bordia, & Tang, 2009).…”
Section: Our View: Envy As Painmentioning
confidence: 99%
“…Such conflicting perceptions create tension and strain (Festinger, 1957;Harmon-Jones, 1999). The concept of social support is quite distinct from abusive supervision, as it supports development of positive relationships while abusive supervision causes negative behaviours (Hobman et al, 2009;Tepper, 2000). To validate this argument, it is worthwhile to mention the study of supervisory undermining conducted by E. Duffy, Michelle, Ganster, and Pagon (2002) in which they found that social support is distinct from supervisory undermining, while the concept of supervisory undermining is closely linked with abusive supervision (Tepper, 2007).…”
Section: Why Does Abusive Supervision Occur?mentioning
confidence: 97%
“…It includes support from a variety of people, e.g., spouse, sibling, friends, peers, supervisors, and neighbours, etc. (Hobman et al, 2009;LaRocco & Jones, 1978). However Arnault (2002) defined social support a bit differently, and linked it with cultural understandings that shape it according to the need, situations/circumstances and the people who need it.…”
Section: Why Does Abusive Supervision Occur?mentioning
confidence: 99%
See 2 more Smart Citations